A comparative study of free and bound bitumens from different mature source rocks with Type III kerogens. (October 2017) - Chen, Jian; Peng, Ping'an
Highlights: Cleavage process of bound molecules from kerogen to free bitumen elucidated. The kerogen is a reliable pool of biomarkers in early-mature and mature stages. The kerogen structure does not retard methyl transfer reactions in aromatic rings. Abstract: The complicated macromolecular structure of kerogen has made it difficult to extract chemical information on bound molecules. The hydropyrolysis (Hypy) technique, which can release considerable amounts of hydrocarbons from kerogen via the mild cleavage method, provides an opportunity to solve this problem. In this study, Type III kerogens with varying degrees of maturation from Lower Carboniferous source rocks in the northern Junggar Basin, China, were subjected to solvent extractions and Hypy experiments. A quantitative comparison of the amount and composition of free and bound bitumen reveals the precise cleavage process of bound molecules from kerogen. As maturation increases, free and bound aliphatic molecules, including biomarkers, decrease markedly as a consequence of continuous cracking and degradation. However, the bound 3-benzene ring compounds are initially enriched and then depleted, consistent with the evolution of the aromatic structure of kerogen. In the early-mature and mature stages, bound bitumen could be a reliable pool of biomarkers, and undoubtedly the bound biomarkers preserve more information about biological inputs. Moreover, due to the protection of the macromolecular structure of kerogen against extreme thermal stress, a few informative biomarkers, especially aliphatic moieties, can be released by Hypy from high-mature kerogens. The rearranged hopane Ts and diasteranes may be present in bound bitumen due to the incorporation of related molecules into the kerogen, possibly during the formation of kerogen. In contrast, C30 rearranged hopane (C30 ∗ ) only occurs in free bitumen due to the catalysis by acidic clays during the mature stage. Side chain and ring isomerization of free and bound hopanes and steranes occurring during maturation is more complicated. For example, the configuration changes from R-dominant, to equilibrium R and S configurations, and then to R configuration dominance again. These changes may be controlled by the generation and degradation processes affecting these compounds. However, most aromatic maturity parameters of the bound fractions increase with maturity (i.e. with increasing %Ro). As documented in the literature, kerogen severely suppresses the chiral isomerization of bound aliphatics, but our results show that it does not retard methyl transfer reactions in aromatic rings.